Dynamic Smoothness Control for Dual-Motor-Independent-Drive Electric Vehicles Based on Kalman Filter. (June 2016) - Lin, Cheng; Dong, Aidao; Shi, Junhui
Abstract: In order to reduce the lateral dynamics shock caused by mechanical gap of a dual-motor-independently-drive electric vehicle while the accelerator pedal was quickly pressed down, the Kalman filter was adopted to design a dynamics smoothness controller. Simulation results proved the effectiveness of the control strategy - it could improve the smoothness of the lateral dynamics effectively. The effect on the control performance of the value of process noise - Q was discussed. It is important to select an appropriate Q to balance the improvement of dynamics smoothness and the increased response time for the accelerator pedal.